Exploring flux-grown transition metal oxynitride perovskites for photocatalytic water oxidation: A minireview - Mirabbos Hojamberdiev; Kenta Kawashima (Energy Reports, 2020)
Transition metal oxynitride perovskites [AB(O,N)3] are an emerging class of inorganic materials with superior light harvesting ability (narrow band-gap energy) and moderate photostability. They can be utilized as visible-light-active photocatalysts for efficient solar water splitting. The photocatalytic activity of transition metal oxynitride perovskites has been significantly improved by changing the synthesis approach, reducing the defect density that acts as a recombination center for photogenerated charge carriers, increasing the conductivity, and engineering their band structures, namely the conduction and valence band positions, through an A/B-site doping/substitution. In this minireview, we briefly overview our recent advances on enhancing the photocatalytic activity of selected transition metal oxynitride perovskites (i.e., LaTiO2N, BaTaO2N, and BaNbO2N) and related works. Additionally, the challenges and future perspectives of these materials are discussed.
Keywords: 330; Oxynitride; Perovskite; Photocatalyst; Solarwater; splitting; Fluxgrowth; Doping; Solidsolution